Injectable hydrogel enables local and sustained co-delivery to the brain: Two clinically approved biomolecules, cyclosporine and erythropoietin, accelerate functional recovery in rat model of stroke. (March 2020) - Tuladhar, Anup; Obermeyer, Jaclyn M.; Payne, Samantha L.; Siu, Ricky C.W.; Zand, Sohrab; Morshead, Cindi M.; Shoichet, Molly S.
Abstract: Therapeutic delivery to the brain is limited by the blood-brain barrier and is exacerbated by off-target effects associated with systemic delivery, thereby precluding many potential therapies from even being tested. Given the systemic side effects of cyclosporine and erythropoietin, systemic administration would be precluded in the context of stroke, leaving only the possibility of local delivery. We wondered if direct delivery to the brain would allow new reparative therapeutics, such as these, to be identified for stroke. Using a rodent model of stroke, we employed an injectable drug delivery hydrogel strategy to circumvent the blood-brain barrier and thereby achieved, for the first time, local and sustained co-release to the brain of cyclosporine and erythropoietin. Both drugs diffused to the sub-cortical neural stem and progenitor cell (NSPC) niche and were present in the brain for at least 32 days post-stroke. Each drug had a different outcome on brain tissue: cyclosporine increased plasticity in the striatum while erythropoietin stimulated endogenous NSPCs. Only their co-delivery, but not either drug alone, accelerated functional recovery and improved tissue repair. This platform opens avenues for hitherto untested therapeutic combinations to promote regeneration and repair after stroke.